SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN PROGRAM KELUARGA HARAPAN (PKH) DI DESA LEKOR MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) BERBASIS WEB - Lalu Puji Indra Kharisma; Sahni Kusmayanti; Yudi Sutaryana (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
Lekor village is one of the villages in janapria district, central Lombok regency, which is located in the southernmost area directly adjacent to east lombok. Currently, lekor village is being shocked by social assistance, especially the family hope program which still uses a manual system, making it difficult to find proper and targeted acceptance. Therefore, it is necessary to develop a Decision Support System as an alternative solution, so as to increase efficiency and ef- fectiveness in the selection and improve quality in determining proper acceptance of assistance. The decision support system for determining accepting PKH assistance uses the SAW (simple additive weighting) method based on predetermined criteria and weights. The criteria used as indicators are the condition of the house, income, the presence of pregnant women and children, the presence of the elderly, and the presence of school children. The SAW (simple additive weighting) method was chosen because it is able to select the best alternative from a number of alternatives. This research was conducted by looking for the weights on each attribute, then ranking to determine the acceptance of the hope family program assistance. In this study using the Waterfall methodology, which is a software development method that begins with ana- lyzing company needs, designing, building applications, to conducting trials. The results of this study are in the form of a decision support application, which can recommend for receiving assistance from the hope family program in lekor village.